APT and TEM study of behaviour of alloying elements in neutron-irradiated zirconium-based alloys. (1st February 2022) - Jenkins, B.M.; Haley, J.; Moody, M.P.; Hyde, J.M.; Grovenor, C.R.M.
Abstract: In this study, APT and TEM analyses were used to characterise two Zr-based alloys neutron-irradiated to 13.7 dpa. The high spatial and chemical resolution of these techniques has enabled the irradiation-induced nanoscale distribution of solute elements to be characterised. The results on both Zircaloy-2 and low-Sn ZIRLO support previous observations of Fe segregation to planar dislocation arrays with enhanced Sn between. In Zircaloy-2, the APT data in this study have also revealed short-range (∼2 nm) clustering of Fe and Sn atoms both within the Fe-enriched planes and in the regions between dislocation arrays. The resultant microstructure is reminiscent of spinodal decomposition. In low-Sn ZIRLO Nb-rich precipitates formed in the Sn-rich planes. The data in this article enhance our understanding of microstructural evolution in Zr alloys under neutron irradiation and are relevant for predicting changes in the properties of Zr alloys in-service in fission reactors. Graphical abstract: Image, graphical abstract